2017
DOI: 10.1002/mus.25498
|View full text |Cite
|
Sign up to set email alerts
|

Intersession reliability of the interpolated twitch technique applied during isometric, concentric, and eccentric actions of the human knee extensor muscles

Abstract: Data indicate that %VA of the knee extensors can be reliably measured during isometric [intraclass correlation coefficient (ICC) = 0.89, coefficient of variation (CV) = 4.1%], concentric (ICC = 0.87, CV = 6.6%), and eccentric muscle actions (ICC = 0.86, CV = 7.0%). Muscle Nerve 56: 324-327, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…The corrected formula is used to avoid the potential problem that the superimposed stimuli are not always applied during the maximum torque level. As shown recently by our group, voluntary activation of the knee extensors can be reliably assessed during isometric contractions using the corrected formula (Behrens et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The corrected formula is used to avoid the potential problem that the superimposed stimuli are not always applied during the maximum torque level. As shown recently by our group, voluntary activation of the knee extensors can be reliably assessed during isometric contractions using the corrected formula (Behrens et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The corrected formula is used to avoid the potential problem that the superimposed stimuli are not always applied during MVT. As shown recently by our group, voluntary activation of the knee extensors can be reliably assessed during isometric contractions using the corrected formula (Behrens et al, 2017).…”
Section: Data Analysesmentioning
confidence: 96%
“…This corrected formula counteracts the problem that the superimposed stimuli are not always applied at the instant of MVT. It has recently been shown that voluntary activation of the knee extensors during isometric MVCs can be reliably assessed using this formula (Behrens et al, 2017). In addition, the central activation ratio (Kent-Braun and Le Blanc, 1996) was calculated as follows: central activation ratio = MVT × (MVT + interpolated twitch torque) −1 × 100.…”
Section: Methodsmentioning
confidence: 99%